MPS 09-08 UTILITY OF N-TERMINAL PRO BRAIN NATRIURETIC PEPTIDE IN DETECTING DIASTOLIC DYSFUNCTION IN ASYMPTOMATIC HYPERTENSIVE PATIENTS: COMPARISON WITH ECHOCARDIOGRAPHY. (September 2016) - Dhungana, Sahadeb Prasad; Karki, Prahlad; Lamsal, Madhab
Abstract : Objective: To assess the role of serum concentration of NT pro-BNP for early detection of diastolic dysfunction in patients with hypertension and to correlate its level with echocardiographic parameters of diastolic dysfunction. Design and Method: Comparative cross-sectional study. Hundred cases of asymptomatic hypertensive patients with normal left ventricular systolic function and 100 healthy subjects were subjected to echocardiography and measurement of serum concentration of NT-pro BNP. Results: Both systolic and diastolic blood pressures were significantly higher (>160/100 mmhg) in cases compared to controls (<120/80 mmHg). The level of mean serum NT-proBNP was significantly higher in patients with hypertension (213.19 + −784.3 pg/ml) compared to healthy controls (58.51 + −11.01 pg/ml) (P = 0.008). There was no significant difference in mean serum NT-proBNP levels between cases with no Left ventricular diastolic dysfunction (n = 15) and controls (n = 100) but it shows statistically significant difference between cases with left ventricular diastolic dysfunction of all grades (n = 86) and controls (n = 100) (P = 0.00). NT-proBNP levels were higher in both group of patients with E/A ratios <0.9 and 0.9–1.5 (245.72 + −366.73 pg/ml and 210.69 + −243.53 pg/ml respectively) as compared to healthy controls (58.51 + 11.01 pg/ml). Mean serum NT-proBNP levels were significantly higher in patients with IVRT >90ms (270.43 + −380.81 pg/ml) as compared to healthy controls (58.51 + −11.01 pg/ml) (P = 0.03) but the difference was not significant between cases with IVRT of 60–90 ms (152.02 + −100.23 pg/ml) and controls (58.51 + −11.01 pg/ml) (P = 0.09). NT-proBNP levels were significantly higher in all group of patients with E/E' ratios <8, 8–12, >12 (197 + −121.25 pg/ml, 263.12 + −422.52 pg/ml and 180 + −106.56 pg/ml respectively) compared to healthy controls (58.51 + −11.01 pg/ml). Conclusions: This study suggests the correlation between echocardiographic parameters of diastolic dysfunction and serum concentration of NT-proBNP. Hence, It may be useful for early detection of LV diastolic dysfunction in asymptomatic hypertensive patients.